Preparation of granular Bi-2212 nanowires by electrospinning. (1st February 2017) - Zeng, Xian Lin; Koblischka, Michael R; Karwoth, Thomas; Hauet, Thomas; Hartmann, Uwe
Abstract: Bi2 Sr2 CaCu2 O8 (Bi-2212) superconducting nanowires are synthesized by the electrospinning method. Two different precursors were employed to grow the nanowires, a Pb-doped one and a Cu, Ca-enriched one. The granular polycrystalline character was confirmed by scanning electron microscopy and x-ray diffraction measurement. The magnetic and electric properties of the samples were investigated via SQUID magnetometry and four-probe resistance measurements. The superconducting transition temperatures of the two systems were found to be similar (Pb-doped 84 K, Cu, Ca-enriched 76 K), but the transition width and the onset of irreversibility were clearly different. The magnetization loops and the resistance data demonstrate that the Cu, Ca-enriched precursor yields samples with better superconducting properties.